The Role of Customer Value, Islamic Brand Preference, and Image on Deposit Decision - Tasya Kemala Mirza; Sudjatno Sudjatno; Sunaryo Sunaryo (University of Merdeka Malang, 2018)
The objective of this study is to examine the direct effect of Syariah brand preference and image on deposit decision, and the indirect effect of its relationship through customer value. About 200 respondents from 4 Syariah state-owned banks in Malang taken as the sample in this study. By using PLS (Partial Least Square) method with Smart PLS 2.0 software, data collected was analyzed to find out the relationship and path coefficients among the variables. Regarding all of the hypotheses that proposed in this study, that is no direct significant relationship of brand preference on deposit decision. Generally, this study reveals the important role of customer value in enhancing the effect of Syariah brand preference and image on deposit decision among Syariah state-owned banks’ customers in Malang. Further discussion, both applied and theoretical recommendations and suggestions for future research directions are shown in this study.JEL Classification: G21; M31; M37DOI: https://doi.org/10.26905/jkdp.v22i2.1341